Scott free [videorecording (DVD)] - Short, Columbus, 1982-; Pearson, Felicia, 1980-; Chaney, Tray (Filmhub, 2023)
This is a story of karma and her revenge on two brothers. One is forever tied to the streets and the other seeks a bigger picture for life. They are trapped inside crime and their own egos.